2020
DOI: 10.3390/v12020133
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting Staphylococcus Phages with Therapeutic and Bio-Control Potential

Abstract: Emergence of antibiotic-resistant bacteria is a serious threat to the public health. This is also true for Staphylococcus aureus and other staphylococci. Staphylococcus phages Stab20, Stab21, Stab22, and Stab23, were isolated in Albania. Based on genomic and phylogenetic analysis, they were classified to genus Kayvirus of the subfamily Twortvirinae. In this work, we describe the in-depth characterization of the phages that electron microscopy confirmed to be myoviruses. These phages showed tolerance to pH rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 52 publications
0
15
0
1
Order By: Relevance
“…The effort and the economic consumption to the development of antimicrobial products ( Chung and Khanum, 2017 ; Hashemi et al, 2018 ), mainly those are effective against MDR strains with metal in the form of a nanoparticle ( Alavi and Rai, 2019 ; Heidary et al, 2019 ; Kumar et al, 2019 ), have promoted the search of new treatments, particularly the treatment of bacteriophages ( Wernicki et al, 2017 ). The bacteriophages are being considered as an alternative to therapy in S. aureus MDR strains (MRSA), S. haemolyticus (MRSH), and Staphylococcus epidermidis (MRSE) infections ( Oduor et al, 2020 ). However, in this study, we found that the CRISPR-Cas system may be a factor that could compromise the efficacy of bacteriophage therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effort and the economic consumption to the development of antimicrobial products ( Chung and Khanum, 2017 ; Hashemi et al, 2018 ), mainly those are effective against MDR strains with metal in the form of a nanoparticle ( Alavi and Rai, 2019 ; Heidary et al, 2019 ; Kumar et al, 2019 ), have promoted the search of new treatments, particularly the treatment of bacteriophages ( Wernicki et al, 2017 ). The bacteriophages are being considered as an alternative to therapy in S. aureus MDR strains (MRSA), S. haemolyticus (MRSH), and Staphylococcus epidermidis (MRSE) infections ( Oduor et al, 2020 ). However, in this study, we found that the CRISPR-Cas system may be a factor that could compromise the efficacy of bacteriophage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…(MRSA, MSSA, Staphylococcus intermedius , S. epidermidis , Staphylococcus saprophyticus , and S. haemolyticus ) strains; moreover, it was found that Stab20 and Stab21 are better spread in some S. aureus strains. The Stab21 bacteriophage is capable to infect an isolated S. aureus from a patient with chronic sinusitis ( Oduor et al, 2020 ). The presence of one SE that matches with Stab20 in the loci CRISPR of the 08BA02176 strain implies that infection with this strain would be difficult, or impossible to treat with a Stab20 bacteriophage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter, randomized controlled study in a population of patients with severe clinical conditions has been conducted with a phage cocktail produced according to good manufacturing practices 17 . The successful use of a good manufacturing practice for the preparation of virulent staphylococcal bacteriophages for intravenous administration was also reported 18 .…”
Section: Introductionmentioning
confidence: 96%
“…The mixtures were incubated at 37°C with shaking at 220 rpm for 60 min. And the phage titer was determined using the DLA method ( Oduor et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%